A minimally-edited mouse model for infection with multiple SARS-CoV-2 strains - Nakandakari-Higa, Sandra; Parsa, Roham; Reis, Bernardo S.; de Carvalho, Renan V. H.; Mesin, Luka; Hoffmann, Hans-Heinrich; Bortolatto, Juliana; Muramatsu, Hiromi; Lin, Paulo. J. C.; Bilate, Angelina M.; Rice, Charles M.; Pardi, Norbert; et al. (Frontiers in Immunology, 2022)
Efficient mouse models to study SARS-CoV-2 infection are critical for the development and assessment of vaccines and therapeutic approaches to mitigate the current pandemic and prevent reemergence of COVID-19. While the first generation of mouse models allowed SARS-CoV-2 infection and pathogenesis, they relied on ectopic expression and non-physiological levels of human angiotensin-converting enzyme 2 (hACE2). Here we generated a mouse model carrying the minimal set of modifications necessary for productive infection with multiple strains of SARS-CoV-2. Substitution of only three amino acids in the otherwise native mouse Ace2 locus (Ace2TripleMutant or Ace2TM), was sufficient to render mice susceptible to both SARS-CoV-2 strains USA-WA1/2020 and B.1.1.529 (Omicron). Infected Ace2TM mice exhibited weight loss and lung damage and inflammation, similar to COVID-19 patients. Previous exposure to USA-WA1/2020 or mRNA vaccination generated memory B cells that participated in plasmablast responses during breakthrough B.1.1.529 infection. Thus, the Ace2TM mouse replicates human disease after SARS-CoV-2 infection and provides a tool to study immune responses to sequential infections in mice.